Biblometric Analysis of Landslide Slope Stability With Geotextile Reinforement Using Vosviewer - Irfan Rifai, Andri; Marselina, Ice; Martin Ginting, Jody (International Journal of Social Service and Research, 2024)
Using biblometrics, this study investigates the relationship between geotextile reinforcement and landslide slope stability. 1000 studies with interrelated topics were created by collecting various studies from 2000 to 2023 using Crossref. Publish or Perish sources were used to run this research network, which was then processed in Vosviewer and saved in Research Information System (RIS) format. The results of the analysis show that slope angle is the most frequently used word and is associated with 63 studies. The results of research conclusion data on the topic of slope stability with geotextile reinforcement continue to increase, with the highest number in 2023 (110 studies).Keyword: Landslides, slope stability, geotextile systems, prediction of landslide management.